Development of a protocol to assess cell internalization and tissue uptake of magnetic nanoparticles by AC Biosusceptometry - Quini, Caio C. [UNESP]; Próspero, André G. [UNESP]; Kondiles, Bethany R.; Chaboub, Lesley; Hogan, Matthew K.; Baffa, Oswaldo; Bakuzis, Andris F.; Horner, Philip J.; Miranda, José R.A. [UNESP] (Elsevier, 2019)
Several applications of nanoparticles rely on the internalization and accumulation of nanocarriers in specific cell compartments and tissues. However, the methods currently employed for characterizing such processes, although well described, are time consuming and do not provide in vivo information, which is a crucial barrier towards translational applications. Here, we hypothesize that the AC Biosusceptometry technique can be employed to assess cell internalization of magnetic nanoparticles, with possible applications in screening assays to track specific biomarkers and cell types. We tested a simpler and easier alternative to study cell internalization and tissue accumulation after perfusion. We utilized citrate coated, manganese ferrite nanoparticles and evaluated the internalization process in mouse macrophages cells (J774.A1) and in an embryonic neural stem cell culture (E14.5) after differentiation in astrocytes and neurons, to assess internalization specificity. Respecting the particles toxicity limits, we tested different concentration of particles, in different incubation times. Sequentially, we imaged the cell cultures to confirm internalization and nanoparticles localization, labeling nucleus and cell body to assure that the particles were inside the cells. Our results showed a linear behavior on internalization for different doses and an optimum incubation time of 2 h.